THE VIRTUES OF SUSTAINABILITY: Jason Kawall - Xiang, Xiaojun (Journal of Dharma, 2022)
This insightful volume, The Virtues of Sustainability, divided into three sections, binds together recently commissioned essays by renowned scholars belonging to a wide array of disciplines spanning philosophy and political science to psychology and religious studies. The first section explores mainly significant factors and structures crucial for fostering the virtues of sustainability. The essays in the second section zoom in on virtues adopted by the non-Western cultures and communities. The third section focuses more on sustainability virtues comprising cooperativeness, conscientiousness, patience, open-mindedness and creativity. Overall, these essays enrich the readers with an understanding of the significance of the virtues of substantiality and real-life guidance to achieving a goal of being a full-rounded, sane-minded, cooperative global citizen.